DISTANCE LEARNING IN MODERN ERA`S EDUCATION SYSTEM: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The main motive behind writing the article is to learn more about what distance learning is and get acquainted readers in more detail with the concept of e-learning in a global context. To be more precise, this article is about to provide clear explanation of distance learning in comparison with traditional way, its merits and demerits.